Case Report: Myelin Oligodendrocyte Glycoprotein Antibody-Associated Relapse With COVID-19 - Woodhall, Mark; Mitchell, James W.; Gibbons, Emily; Healy, Sarah; Waters, Patrick; Huda, Saif (Frontiers in Neurology, 2020)
A 39-year-old lady with relapsing myelin oligodendrocyte glycoprotein antibody (MOG-IgG) associated demyelination developed coryzal symptoms, malaise, sweating and postural dizziness. Six days later she presented with painful progressive right visual loss consistent with optic neuritis. COVID-19 was confirmed by nasopharyngeal swab and MOG-IgG serological reversion was noted. Vision function improved following steroids and plasma exchange. This case highlights a possible causal association between inflammation due to COVID-19 and a relapse of MOG-IgG associated disease. It also highlights the clinical relevance of reporting MOG-IgG titres in MOG-IgG associated demyelination.